Impact of continuous cropping on microbial biomass and enzyme activities in the surface layer of gravel-sand mulched soils in arid Northwest China: A Meta-analysis - XUE Yinmin; JIA Zhenjiang; MA Dongxiang; WU Yangyang; HUANG Yahao; HE Xuezhong; WU Xiu; LI Wangcheng (Guan'gai paishui xuebao)
【Objective】Soil microorganisms and enzymes play crucial roles in nutrient cycling and maintaining soil health, and their activities are influenced by various abiotic and biotic factors. This study uses meta-analysis to investigates the impact of long-term continuous cropping on microbial biomass and enzyme activities in the surface layer of gravel-sand mulched soils in arid regions of Northwestern China.【Method】Microbial indicators extracted from the literature included total bacterial count (TBC), total fungal count (TFC), total actinomycetes count (TAC), total microbial count (TMC), the bacteria-to-fungi ratio (TBC∶TFC), microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), and the MBC∶MBN ratio. Enzymatic indicators extracted from the literature were activities of catalase (CAT), urease (URE), phosphatase (PHO), and sucrase (SUR). Fields mulched with gravel for 1-3 years served as the control (CK). Pearson correlation analysis was used to examine the relationships between microbial activity and soil nutrient factors such as soil organic matter (SOM), total nitrogen (TN), total phosphorus (TP), available nitrogen (AN), available phosphorus (AP), and available potassium (AK).【Result】Compared to the control, long-term continuous cropping (4-15 years) significantly (P＜0.05) reduced TBC, TFC, TAC, TMC, TBC∶TFC, MBC, MBN, MBC∶MBN, and the activities of URE, PHO, and SUR by 39.35%, 12.99%, 58.34%, 42.13%, 30.11%, 56.43%, 25.45%, 32.75%, 40.77%, 18.42%, and 32.89%, respectively. These negative effects intensified with increasing cropping duration. In contrast, continuous cropping increased CAT activity by an average of 1.27% (P＜0.05), likely due to the changes in soil nutrients.【Conclusion】Continuous cropping for 4-6 years significantly affects topsoil microbial activity in gravel-sand mulched fields, leading to early signs of soil degradation. These findings highlight the need for optimized cropping strategies and improving soil management to sustain microbial function and soil fertility in arid and semi-arid agricultural systems in Northwestern China.